Expression, purification and characterization of soluble human thrombopoietin receptor from Escherichia coli - Park, H; Im, H; Kang, YJ; Yu, MH; Hong, HJ (KLUWER ACADEMIC PUBL, 2000)
The extracellular domain (edMpl) of human thrombopoietin (TPO) receptor, c-Mpl was expressed in Escherichia coli by changing some nucleotides before and after the translation initiation codon. The mutations increased the expression by approx. 15-fold. The inclusion bodies were solubilized in 8 M guanidine-HCl under reducing conditions and refolded using a glutathione-redox system. The monomeric form of edMpl was purified to near homogeneity by two successive steps of ion-exchange chromatography using DEAE-Sephacel and Mono Q columns. The purified monomeric edMpl inhibited the TPO-dependent cell proliferation, suggesting that it was binding to TPO. Also, antisera raised against the edMpl bound specifically to the soluble receptor secreted by mammalian cells.
Keywords: C-MPL LIGAND; IDENTIFICATION; CLONING; STIMULATION; GROWTH; CODON